Electrocaloric effect in La-doped BNT-6BT relaxor ferroelectric ceramics - Li, Lucheng; Xu, Mengxing; Zhang, Qi; Chen, Ping; Wang, Ningzhang; Xiong, Dingkang; Peng, Biaolin; Liu, Laijun (Elsevier, 2017)
Relaxor [(Bi1/2Na1/2)0.94Ba0.06](1-1.5x)LaxTiO3 (x = 0, 0.03, 0.06, 0.09) ceramics (La-doped BNT-6BT) with composition close to the morphotropic phase boundary (MPB) were successfully prepared by using the conventional solid state reaction method. All samples present almost a pure perovskite phase with the coexistence of tetragonal and rhombohedral. With the increase of La doping content, the degree of the dielectric relaxor dispersion around the dielectric peak which is close to the room temperature increases, and also the transition temperature of ferroelectric-to-relaxor (TF-R) shifts 120 K towards a lower temperature at x = 0.09. The maximum value of the temperature change (ΔT) of the electrocaloric (EC) effect decreases sharply from 1.1 K at x = 0–0.064 K at x = 0.09. A large positive EC effect (maximum ΔT ~ 0.44 K) in a broad temperature range (~ 90 K) close to room temperature is achieved at x = 0.03, indicating that it is a promising lead-free material for application in solid state cooling system. Moreover, it is found that the Maxwell relationship can be well used to assess the EC effects of the La-doped BNT-6BT ceramics when the operating temperature is higher than that of the TF-R, indicating that these relaxor ceramics would perform as an ergodic.
Keywords: Relaxor ferroelectric; Electrocaloric; MPB; Lead-free